A molecular war: convergent and ontogenetic evidence for adaptive host manipulation in related parasites infecting divergent hosts. Issue 1915 (20th November 2019) - Herbison, Ryan; Evans, Steven; Doherty, Jean-François; Algie, Michael; Kleffmann, Torsten; Poulin, Robert
Abstract : Mermithids (phylum Nematoda) and hairworms (phylum Nematomorpha) somehow drive their arthropod hosts into water, which is essential for the worms' survival after egression. The mechanisms behind this behavioural change have been investigated in hairworms, but not in mermithids. Establishing a similar mechanistic basis for host behavioural change between these two distantly related parasitic groups would provide strong convergent evidence for adaptive manipulation and insight into how these parasites modify and/or create behaviour. Here, we search for this convergence, and also contrast changes in physiology between hosts infected with immature and mature mermithids to provide the first ontogenetic evidence for adaptive manipulation by disentangling host response and pathology from the parasite's apparent manipulative effects. We used SWATH-mass spectrometry on brains of Forficula auricularia (earwig) and Bellorchestia quoyana (sandhopper), infected with the mermithids Mermis nigrescens and Thaumamermis zealandica, respectively, at both immature and mature stages of infection, to quantify proteomic changes resulting from mermithid infection. Across both hosts (and hairworm-infected hosts, from earlier studies), the general function of dysregulated proteins was conserved. Proteins involved in energy generation/mobilization were dysregulated, corroborating reports of erratic/hyperactive behaviour in infected hosts. Dysregulated proteins involved in axon/dendrite and synapse modulation were also common to all hosts, suggesting neuronal manipulation is involved in inducing positive hydrotaxis. Furthermore, downregulation of CamKII and associated proteins suggest manipulation of memory also contributes to the behavioural shift.